2019
DOI: 10.3389/fmicb.2019.00166
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Microbial Maintenance in Acetogenesis and Methanogenesis by Experimental and Modeling Techniques

Abstract: For biogas-producing continuous stirred tank reactors, an increase in dilution rate increases the methane production rate as long as substrate input can be converted fully. However, higher dilution rates necessitate higher specific microbial growth rates, which are assumed to have a strong impact on the apparent microbial biomass yield due to cellular maintenance. To test this, we operated two reactors at 37°C in parallel at dilution rates of 0.18 and 0.07 days-1 (hydraulic retention times of 5.5 and 14 days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Thus, the numbers have possibly been underestimated, as DNA extractions from soils may provide less than 100% yields, qPCR quantification can be inhibited by soil-derived impurities in the DNA extract, and primer mismatches can result in an underrepresentation of copy numbers. Methanogenic archaea and acetogenic bacteria were recently found to require much less maintenance energy (0.2 kJ Cmol h −1 ) than previously believed (9.8 kJ Cmol h −1 ) [ 29 ]. According to the authors, the low maintenance energy was based on the low growth rates of these organisms, a feature that had not previously been taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the numbers have possibly been underestimated, as DNA extractions from soils may provide less than 100% yields, qPCR quantification can be inhibited by soil-derived impurities in the DNA extract, and primer mismatches can result in an underrepresentation of copy numbers. Methanogenic archaea and acetogenic bacteria were recently found to require much less maintenance energy (0.2 kJ Cmol h −1 ) than previously believed (9.8 kJ Cmol h −1 ) [ 29 ]. According to the authors, the low maintenance energy was based on the low growth rates of these organisms, a feature that had not previously been taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…Modified mineral medium DSMZ1036 containing yeast extract (0.2 g L −1 ), as described by Porsch and colleagues [36], was used for the enrichment and is designated as medium A hereafter. For further experiments, the medium was used in two variants: medium B did not contain yeast extract, but was supplemented with a vitamin solution, as described by [37], and cysteine-HCl as reducing agent in the same concentration as in medium A. Medium C contained vitamins, like medium B, but sodium sulfide as a reducing agent, as described by [37].…”
Section: Growth Mediummentioning
confidence: 99%
“…For further experiments, the medium was used in two variants: medium B did not contain yeast extract, but was supplemented with a vitamin solution, as described by [37], and cysteine-HCl as reducing agent in the same concentration as in medium A. Medium C contained vitamins, like medium B, but sodium sulfide as a reducing agent, as described by [37]. After preparing the media as described in Text S1 (Supplementary Materials), the pH for all media variations was adjusted to nine with a sterile anoxic stock solution of 2 M KOH.…”
Section: Growth Mediummentioning
confidence: 99%
“…While higher values have been estimated before, including 0.9 mmol ATP/gDW/h for M. maripaludis , and 3.6 mmol ATP/gDW/h for acetate converting M. barkeri [collected in (Koch et al (2016)], maintenance energies have also been reported to be lower than theoretical predictions under methanogenic conditions (Scholten and Conrad, 2000). A combination of experimental and modeling approaches has recently suggested even smaller values of below 0.116 mmol ATP/gDW/h for short hydraulic retention times, likely being applicable to also longer hydraulic retention times (Bonk et al, 2019). Fitting with this observation, maintenance demands in a binary propionate utilizing syntrophic methanogenic culture were experimentally determined to be 0.14 mmol ATP/gDW/h for Syntrophobacter fumaroxidans and 0.025 mmol ATP/gDW/h for Methanospirillum hungatei (Hamilton et al, 2015).…”
Section: Discussionmentioning
confidence: 99%